Variation in the costs of delivering routine immunization services in Peru - D. Walker; N. R. Mosqueira; M.E. Penny; C.F. Lanata; A.D. Clark; C.F.B. Sanderson; J.A. Fox-Rushby (The World Health Organization, 2004)
OBJECTIVE: Estimates of vaccination costs usually provide only point estimates at national level with no information on cost variation. In practice, however, such information is necessary for programme managers. This paper presents information on the variations in costs of delivering routine immunization services in three diverse districts of Peru: Ayacucho (a mountainous area), San Martin (a jungle area) and Lima (a coastal area). METHODS: We consider the impact of variability on predictions of cost and reflect on the likely impact on expected cost-effectiveness ratios, policy decisions and future research practice. All costs are in 2002 prices in US$ and include the costs of providing vaccination services incurred by 19 government health facilities during the January-December 2002 financial year. Vaccine wastage rates have been estimated using stock records. FINDINGS: The cost per fully vaccinated child ranged from US$ 16.63-24.52 in Ayacucho, US$ 21.79-36.69 in San Martin and US$ 9.58-20.31 in Lima. The volume of vaccines administered and wastage rates are determinants of the variation in costs of delivering routine immunization services. CONCLUSION: This study shows there is considerable variation in the costs of providing vaccines across geographical regions and different types of facilities. Information on how costs vary can be used as a basis from which to generalize to other settings and provide more accurate estimates for decision-makers who do not have disaggregated data on local costs. Future studies should include sufficiently large sample sizes and ensure that regions are carefully selected in order to maximize the interpretation of cost variation.